2020
DOI: 10.1017/qua.2020.82
|View full text |Cite
|
Sign up to set email alerts
|

A wetland oasis at Wadi Gharandal spanning 125–70 ka on the human migration trail in southern Jordan

Abstract: Former lakes and wetlands can provide valuable insights to the late Pleistocene environments encountered by the first humans to enter the Levant from Africa. Fluvial incision along Wadi Gharandal in hyperarid southern Jordan has exposed remnants of a small riverine wetland that accumulated as a sedimentary sequence up to ~20 m thick. We conducted a chronometric and sedimentological study of this wetland, including 10 optically stimulated luminescence dates. The wetland sequence accumulated during the period ~1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 79 publications
2
11
0
Order By: Relevance
“…The accumulation of reworked, secondary fluvial loess continued at Jurf ed Darawish until at least 30 ka before erosion started to prevail sometime afterwards. The new data from Jurf ed Darawish and published information from other locations in the southern Levant show that streams and in-stream and spring-fed wetlands occurred on the Jordanian Plateau, in Wadi Arava/Araba and in the Negev in the Late Pleistocene (Schwarcz et al, 1979;Waldmann et al, 2010;Winer, 2010;Al-Saqarat et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The accumulation of reworked, secondary fluvial loess continued at Jurf ed Darawish until at least 30 ka before erosion started to prevail sometime afterwards. The new data from Jurf ed Darawish and published information from other locations in the southern Levant show that streams and in-stream and spring-fed wetlands occurred on the Jordanian Plateau, in Wadi Arava/Araba and in the Negev in the Late Pleistocene (Schwarcz et al, 1979;Waldmann et al, 2010;Winer, 2010;Al-Saqarat et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…90 km southwest of Jurf ed Darawish, were regarded as formed in the Pleistocene Lake Lisan by Bender (1968). The recent reassessment by Al-Saqarat et al (2021) revealed that the sediments represent a wetland sequence accumulated in the wadi between ca. 125-70 ka.…”
Section: Comparison With Other Pleistocene Records In the Regionmentioning
confidence: 99%
“…This might be the result of difficulties in stratigraphic correlations between the two cores and/or lateral variation of depositional environments. However, this discrepancy can also depend on intrinsic problems with radiocarbon dating of organic-rich sediments (Lai et al, 2014;Al-Saqarat et al, 2021) in a playa or playa lake environment, where carbonates are constantly forming and dissolving following complex biogeochemical patterns and pH changes.…”
Section: Age Of the Sediments At The Kubu Sitementioning
confidence: 99%
“…The radiocarbon dating method is regarded as a reliable dating method with an age limit, theoretically, up to approximately 55,000 years (Hajdas et al, 2021). However, a growing number of geochronologic studies corroborated that the reliability of radiocarbon dating for late Pleistocene sediments is problematic due to the age limit cluster around 35-40 ka BP (Yim et al, 1990;Pigati et al, 2007;Yi et al, 2013;Wang et al, 2018a;Miller and Andrews, 2019;Agatova et al, 2020;Al-Saqarat et al, 2021), or approximately 25 ka BP in practice Wang et al, 2014;Song et al, 2015;Li et al, 2020c;Cheng et al, 2022;Long et al, 2022). The optically stimulated luminescence (OSL) dating method has become widely accepted in recent decades, with its merits of a long time-scale range (even up to 200 ka) and abundance of dating materials (e.g., quartz or feldspar) (Murray and Olley, 2002;Rhodes, 2011;Murray et al, 2021).…”
Section: Introductionmentioning
confidence: 99%